(untitled) (Journal of Informatics Education and Research, 2026)
This study investigates the factors influencing professional success and career development across five key domains: Educational Attainment & Skill Development, Career Entry & Early Opportunities, Professional Growth & Leadership Advancement, Networking, Mentorship & Social Capital, and Workplace Environment & Sustainability of Success. The aim of the research is to examine how educational preparation, early career conditions, leadership development experiences, social capital, and workplace practices collectively shape the career trajectories of individuals. A sample of 184 respondents was surveyed using a structured Likert-scale questionnaire to collect relevant data. The study employed a quantitative research design to analyse variables such as field choice, research experience, digital skills, extracurricular involvement, job timing, employer type, job conversion, networking, job satisfaction, award recognition, leadership training, project visibility, career mobility, mentor quality, alumni support, association membership, online presence, pay equity, workplace safety, job engagement, and employee retention. The findings reveal that strong educational skill development—particularly digital competencies and active extracurricular involvement—significantly enhances early career opportunities and job satisfaction. Networking and mentorship were also found to play a vital role in advancing leadership potential, with respondents reporting higher career mobility when supported by mentors and alumni networks. Furthermore, workplace environment factors such as pay equity, safety, and engagement emerged as strong predictors of long-term employee retention. No major disparities were observed across different employer types, but respondents with higher digital proficiency and stronger social capital reported more positive career progression. The study concludes with recommendations for educational institutions, employers, and policymakers to strengthen career pathways by enhancing skill development programs, promoting mentorship networks, and improving workplace practices to support sustainable professional growth.